Does Inward Foreign Direct Investment Affect Productivity across Industries in Korea? - Yong Joon Jang (East Asian Economic Review, 2021)
This paper empirically examines whether and how inward foreign direct investment (FDI) affected industrial productivity in Korea during the 2000-2016 period, based on dynamic panel data of inflow FDI on an arrival basis from 427 manufacturing industries. The paper adds to the literature by analyzing whether both technology spillovers and industrial restructuring from inward FDI can differ according to industrial characteristics such as capital intensity, imported intermediate inputs, and tariffs. The empirical results show that the overall effects of inward FDI on total factor productivity (TFP) were statistically insignificant in general. However, the positive effects of inward FDI on productivity became statistically significant for industries with lower tariffs. Capital intensity were not involved in the relationship between inward FDI and productivity. Thus, the paper highlights that the results in previous studies with inward FDI on a notification basis were overestimated and inward FDI policies in Korea should focus on channels such as trade liberalization and the redistribution of production factors rather than capital accumulation.